Factors That Influence The Nurse Performanceinpatienroom At Rumah Sakit Umum Daerah Haji Abdul Manan Simatupang 2022 - Pranata, Roby; Donal Nababah; Johansen Hutajulu (Fakultas Keperawatan dan Fisioterapi Institut Kesehatan Medistra Lubuk Pakam, 2023)
Nursesasoneofhealthworkersinthehospitalhavinganimportantrolein achieving health development goals. The success of health services depends ontheparticipation of nursesto providehighqualitycare nursingfor patients . The type of research used in this research is quantitative with a cross sectional study approach. With the aim of assessing factors related to the performance of inpatient ward nurses at Haji Abdul Manan Simatupang Hospital in 2022. And the sampling technique used a total sample and data collection was carried out using questionnaires and univariate, bivariate, and multivariate data analysis using the SPSS program. The results showed that workload (p=0.046), work stress (p=0.036) and incentives (p=0.013) were related to nurse performance. After multivariate analysis, the most influential variable on the performance of inpatient nurses at Haji Abdul Manan Simatupang Hospital in 2022 was incentive (p = 0.013). The conclusion is obtained that there is a relationship between workload, work stress, and incentives that have a relationship with the performance of the inpatient nurse at Haji Abdul Manan Hospital Simatupang. For this reason, it is necessary to improve nursing services that can be pursued by improving the performance of nurses, namely by increasing knowledge through continuous nursing education and improving nursing skills is absolutely necessary. Structuring a conducive work environment needs to be created so that nurses can work effectively and efficiently. Increasing the incentives of nurses is the most influential push on the performance of nurses.